Early childhood education and complexity: an overview of brazilian research (Research, Society and Development, 2021)
The present study is characterized as State-of-the-art research, and had the intention its goal is to understand how the production of knowledge in the area field of Early Childhood Education takes place, from the perspective of complexity, based on research already carried out, realizing its approaches and perspectives. In this study, the methodological procedures based on the steps proposed by Romanowski (2002) were associated and the data analysis that took place from Franco (2005). In the first stage of the research, a survey of theses and dissertations was carried out in the Brazilian Digital Library of Theses and Dissertations, which contained the descriptors early childhood education and complexity, resulting in 143 researches. After applying the inclusion and exclusion criteria, the corpus of analysis consisted of 09 researches, which allowed relating the research stages using the complexity principles proposed by Morin (2003). From the data analysis, it was noticeable a weakness and superficiality of the researches in the area, and the need to deepen the studies about this theme.